Results of a retrospective analysis to identify the causes of nephropathologies in prenatal children exposed to maternal inflammatory process of bacterial etiology of the genitourinary system - Mishyn, Yurii; Myroshnychenko , Mykhailo; Mishyna, Maryna; Marchese, Alessandra; Pisi , Roberta; Bondarenko, Olha; Aiello, Marina; Chetta, Alfredo (Acta Biomedica Atenei Parmensis, 2025)
Background and Aim. Urinary tract infection during pregnancy is one of the most common infections in women. Nearly two-thirds of babies are born with kidney disease due to prenatal exposure to inflammation in the mother. Determining the risk of developing kidney disease is important to prevent complications. The aim of this study is to determine the causes and criteria for the occurrence of specific manifestations of nephropathology in children of different ages and genders, based on a retrospective analysis of archival documentation. Methods. Retrospective cohort study included archival documentation of 76 cases of kidney diseases in children of various ages born to mothers whose pregnancies occured against the background of inflammatory diseases of the genitourinary system of bacterial etiology. Results. The occurence of kidney diseases in children depends on age and gender. Kidney diseases were detected in girls of the older age group in 67.1% of cases. The debut of nephropathy from birth was detected in 28.4 % of cases. Manifest kidney diseases at an early age was detected in 23.7% of cases. In 93.4% of cases combined kidney pathologies were registered. Conclusion. The frequency of nephropathology in children of different ages is associated with the presence of an infectious process of the genitourinary system of bacterial etiology in women during pregnancy. The early risk of nephropathology in children is associated with an infectious disease of the genitourinary system of the mother during pregnancy. The manifestation of inflammation in the presence of a complex perinatal history occurs at birth or in early childhood.